Paediatric snakebite envenoming: the world's most neglected 'Neglected Tropical Disease'? - Pach, Sophie (2020)
Snakebite disproportionally affects children living in impoverished rural communities. The WHO has recently reinstated snakebites on its list of Neglected Tropical Diseases and launched a comprehensive Strategy for the Prevention and Control of Snakebite Envenoming. In the first of a two paper series, we describe the epidemiology, socioeconomic impact and key prevention strategies. We also explore current challenges and priorities including the production and distribution of safe and effective antivenom.